2011
DOI: 10.1002/ijc.25547
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of mesothelioma by detection of manganese‐superoxide dismutase activity using manganese‐enhanced magnetic resonance imaging

Abstract: Malignant mesothelioma (MM) is a fatal malignancy with a rapidly increasing incidence in industrialized countries because of the widespread use of asbestos in the past centuries. Early diagnosis of MM is critical for a better prognosis, but this is often difficult because of the lack of disease-specific diagnostic imaging. Here, we report that manganese-enhanced magnetic resonance imaging (MEMRI) represents a promising approach for a more selective mesothelioma imaging by monitoring a high-level expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Several studies have measured the T1 in tumors after the injection of MnCl2. The limitation of these studies was the acquisitions of T1 maps in 2D on a limited number of slices through the tumors212223. Only a few studies acquired T1 maps in 3D, with the main drawback of long acquisition times: from 40 min24 to ~2 h25.…”
mentioning
confidence: 99%
“…Several studies have measured the T1 in tumors after the injection of MnCl2. The limitation of these studies was the acquisitions of T1 maps in 2D on a limited number of slices through the tumors212223. Only a few studies acquired T1 maps in 3D, with the main drawback of long acquisition times: from 40 min24 to ~2 h25.…”
mentioning
confidence: 99%
“…Our results here agreed well with our previous results of greater enhancement by MEMRI of mesotheliomas with higher levels of Mn-SOD-expression. 5 In addition, because we have shown comparable results between MEMRI using manganese dipyridoxyldiphosphate (MnDPDP), a Mnchelating contrast agent used clinically, and MEMRI using MnCl 2 , 5 our studyˆndings have clinical implications.…”
Section: Discussionmentioning
confidence: 75%
“…Our recent report that MEMRI could be used to detect mesothelioma with high expression of Mn-SOD suggested the possible preferential enhancement of tumors overexpressing Mn-SOD by MEMRI. 5 Here, we further evaluate the usefulness of MEMRI in tumor detection and investigate the eŠects of Mn-SOD expression in tumor enhancement by MEMRI.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding exposure to asbestos, MRI could be regarded as suitable for potentially repeated examinations following initial screening by CT. 138,139 In an experimental model of malignant mesothelioma, Hasegawa et al 140 reported the use of manganese-enhanced MRI (MEMRI) for selective mesothelioma imaging in vivo. The authors made use of the high-level expression of manganese-superoxide dismutase (Mn-SOD) observed in malignant mesotheliomas to induce accumulation of manganese (Mn 21 ) ions in tumors, resulting in significant T 1 signal enhancement in vitro and in vivo in xenografted pleural tumors (Figure 17.10).…”
Section: Side Effects From Inhaled Pollutants or Particlesmentioning
confidence: 99%